O-035 Outcomes of basilar artery occlusion (BAO) in different healthcare facilities: a nationwide descriptive study. (22nd July 2018) - Zafar, A; Ikram, A; Qeadan, F; Bzdyra, P; Nunez-Gonzalez, J; Calder, C; Ortega-Gutierrez, S
Abstract : Basilar artery occlusion (BAO) in the posterior circulation is associated with high morbidity and mortality. It is anticipated that early recanalization with intra-arterial thrombectomy (IAT) is associated with improved outcome in BAO, as is true for anterior circulation stroke. Disease burden and outcome measures among BAO patients in rural, urban non-academic and academic centers is not well studied. This is the first ever study reporting clinical outcome in BAO patients who underwent IAT vs no IAT, presenting at academic versus non-academic centers. This is a descriptive, cross-sectional study using data from the National Inpatient Sample database (Jan 2014-Sep 2015). We ICD-9 codes to identify the diagnosis of basilar artery occlusion (433.01) and IAT (39.74) procedure. Multiple regression with complex design was used to evaluate total hospital charge, length of stay (LOS) and disposition. Statistical analysis performed by the SAS version 9.4, Cary, NC, USA. We identified 1120 patients (40% females) with BAO. Majority of the patients (82%) with BAO were managed in academic Hospitals, with one-fourth (250/919) of these BAO patients being accepted transfers. Basic demographics, worse outcome indicators, and vascular risk factors of BAO are described in table 1. We compared LOS, cost of care (total charge of stay) and disposition of patients as shown in table 2. Sixteen percent (184/1120) patients received IAT with longer LOS, worse outcome (mortality ˜40%) in this group compared to the medical management group (mortality ˜18%). There is a trend towards a worse outcome in BAO patients receiving IAT, compared to those receiving medical management. This may be due to the bias that critical patients were offered IAT or due to delays in transfers. Further large-scale prospective studies are needed. Disclosures: A. Zafar: None. A. Ikram: None. F. Qeadan: None. P. Bzdyra: None. J. Nunez-Gonzalez: None. C. Calder: None. S. Ortega-Gutierrez: None.